Long-acting hydrogel/microsphere composite sequentially releases dexmedetomidine and bupivacaine for prolonged synergistic analgesia. (October 2018) - Zhang, Wenjing; Xu, Weiguo; Ning, Cong; Li, Mingqiang; Zhao, Guoqing; Jiang, Weiqian; Ding, Jianxun; Chen, Xuesi
Abstract: Local anesthetics are a class of drugs, which have wide applications in the treatment of acute and chronic pain. However, their analgesic effects only last for a few hours because of their short half-life, which is insufficient for clinical application, especially for long-term surgery or postoperative analgesia. Herein, an injectable hydrogel/microsphere (GEL/MS) composite co-encapsulating bupivacaine (BUP) and dexmedetomidine (DEX) was developed for effective sustained analgesia. The GEL/MS composite appeared as a three-dimensional porous network microstructure and displayed sustained sequential release of DEX and BUP over several days in vitro, without obvious burst release. In this composite, DEX was released from the GEL matrix preferentially, exhibited long-term vasoconstriction effect and improved the local anesthetic concentration at injection site by preventing BUP from diffusing into the blood circulation. BUP was released subsequently from the MS for blockage of the Na + channel on nerve cell membranes and provided long-term analgesia. In vivo analgesic effect demonstrated that DEX significantly prolonged the effect of analgesia when synergistically administered with BUP in the GEL/MS composite. Moreover, the GEL/MS composite exhibited good biodegradability and biocompatibility in histological analyses. Taken together, the administration of BUP and DEX in the GEL/MS composite achieved a synergistic effect in prolonging analgesia without causing toxicity, and thus represented a potential strategy for long-acting analgesia therapy. Graphical abstract: Image 1